Brain-Gain Directors, Board Gender Diversity, and Firm Performance - Shu-Fen Chuah; Char-Lee Lok; Chee-Wooi Hooy (SAGE Open)
Using a sample of 5,039 hand-collected panel data from Bursa Malaysia spanning 2009 to 2015, this study examines the impact of brain-gain directors (i.e., foreign directors and returnee directors) on firm performance. A two-step robust system GMM is implemented to control for data endogeneity. In line with the resource-based theory, the findings show that brain-gain directors are positively associated with firm performance. Specifically, for each additional foreign director or returnee director on the board, firm performance is expected to increase by an average of 7.41% and 3.23%, respectively. This indicates that a director’s foreign exposure and connectivity are valuable firm resources, with foreign-born directors contributing more significantly to firm performance due to their greater international experience and resources compared to returnee directors. However, further analysis reveals that this positive relationship diminishes when the board consists solely of males, suggesting that gender diversity on the board is essential for brain-gain directors to effectively contribute. A diverse range of directors across borders (e.g., nationality and international working/tertiary education background) and genders represents a spectrum of assets that could potentially provide competitive advantages to firms. The results align with the resource-based theory and support the implementation of brain gain and corporate governance policies that encourage greater female representation on boards. JEL Classification: G3, G34, M14, M51, I28, J18.